Translation and Validation of Pediatric Balance Scale in Urdu Language Among Attention Deficit Hyperactive Disorder - Kaynat Khadim, Shoaib Waqas, Rida Khawar Dar, Qurat Ul Ain Sherazi, Muhammad Tariq, Hafiz Muhammad Asim (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To Translate and validate Pediatric balance scale in Urdu language among Attention Deficit Hyperactive Disorder population. Methods: This was descriptive linguistic validation study with non probability sampling technique consisted on five phases. In first phase, translation of original pediatric balance scale (PBS) was translated into target language Urdu by two independent translators (T1, T2), one from Urdu educational background and other one from pediatric practicing medical professional (Forward Translation). In second phase, the two translated versions (T1, T2) were backward translated by two independent translators (T3, T4), one from English educational background and other one from pediatric practicing medical professional (Backward Translation). In the third phase, forward and backward versions were compared to the original version, and discrepancies were resolved, the format was changed, inappropriate terms were rejected, and the equivalence of the original and final versions was verified by an expert committee at the end of the process and generated (T5) final version. In the fourth phase, data was obtained from 20 clinical pediatric professionals for validity testing using the Final translated version (T5). In the fifth phase, data was collected from ADHD parents and caregivers who came to hospitals and special schools with prior consent and met the inclusion criteria for reliability. Results: The mean age of parents and care givers was 46.52 and standard deviation was 0.9674. The content validity of Translated version Urdu (T5) was 0.86 which seems to be acceptable. The calculated Chronbach’s alpha was 0.966 which is measuring correlations between different items on the PBS. Test re-test reliability ranged from 0.616-0.950 which means information remained consistent over brief periods. Intra-class correlation coefficient value ranged from 0.897 - 0.974 with statically significant value. Conclusion: Urdu version of Pediatric Balance Scale is reliable and valid tool for the assessment of balance in Attention Deficit Hyperactive Disorder.